Analysis of GPU Power Consumption Using Internal Sensors - Ferro, Mariza; Yokoyama, André; Klôh, Vinicius; Silva, Gabrieli; Gandra, Rodrigo; Bragança, Ricardo; Bulcão, Andre; Schulze, Bruno (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2017)
GPUs has been widely used in scientific computing, as by offering exceptional performance as by power-efficient hardware. Its position established in high-performance and scientific computing communities has increased the urgency of understanding the power cost of GPU usage in accurate measurements. For this, the use of internal sensors are extremely important. In this work, we employ the GPU sensors to obtain high-resolution power profiles of real and benchmark applications. We wrote our own tools to query the sensors of two NVIDIA GPUs from different generations and compare the accuracy of them. Also, we compare the power profile of GPU with CPU using IPMItool.